2003
DOI: 10.1007/s00445-003-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic tremor related to the 1991 eruption of the Hekla volcano, Iceland

Abstract: Volcanic tremor at the Hekla volcano is directly related to eruptive activity. It starts simultaneously with the eruptions and dies down at the end of them. No tremor at Hekla has been observed during noneruptive times. The 1991 Hekla eruption began on 17 January, after a short warning time. Local seismograph stations recorded small premonitory earthquakes from 16:30 GMT on. At 17:02 GMT, low-frequency volcanic tremor became visible on the seismograph records, marking the onset of the eruption. The initial pli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…1), data are available from 17 h until midnight of February 26, and from 3-7 h on February 27. SAU is an especially useful station regarding the onset of the eruption, because continuous data recorded at SAU also exist for the first hours of the 1991 eruption, and the two cases can thus be compared (see Soosalu and Einarsson (2002) and Soosalu et al (2003)). There are continuous records available from stations GYG 40 km northwest of Hekla, MID 40 km to the south-southwest, SKR 90 km to the northeast, and ASB 115 km to the northwest until 21 h on February 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), data are available from 17 h until midnight of February 26, and from 3-7 h on February 27. SAU is an especially useful station regarding the onset of the eruption, because continuous data recorded at SAU also exist for the first hours of the 1991 eruption, and the two cases can thus be compared (see Soosalu and Einarsson (2002) and Soosalu et al (2003)). There are continuous records available from stations GYG 40 km northwest of Hekla, MID 40 km to the south-southwest, SKR 90 km to the northeast, and ASB 115 km to the northwest until 21 h on February 26.…”
Section: Discussionmentioning
confidence: 99%
“…The 2000 eruption is the fourth in a row of relatively small eruptions occurring approximately once a decade, which has been the recent pattern in the activity of Hekla. The previous eruptions were in 1970(Einarsson and Björnsson 1976), 1980(Grönvold et al 1983) and 1991(Gu›mundsson et al 1992Soosalu and Einarsson 2002;Soosalu et al 2003). These eruptions are rather similar regarding chemical composition and volume of the products (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…The South Iceland Lowland (SIL) project was originally aimed at recording the magnitude and the location of earthquakes occurring along the SISZ. The 1991 Hekla eruption showed that the use of the SIL network of seismograph stations can be extended, beyond the normal recording of earthquake activity, to study the intensity and amplitude of volcanic tremor in different frequency bands Soosalu et al 2003). The same investigation was repeated during the Hekla 2000 eruption H.…”
Section: Volcanic Tremor and Evolution Of The Reflected Plume And Promentioning
confidence: 99%
“…The earthquake swarm began at 16:30 (Figure 6) with small events, which quickly became larger until the eruption broke out between 17:00 and 17:02 (Gudmundsson et al, 1992;Linde et al, 1993;Soosalu and Einarsson, 2002;Soosalu et al, 2003). The recorded seismic activity was detected by people before the eruption was seen, but only after the eruption had already started.…”
Section: Heklamentioning
confidence: 99%
“…Plot of tremor amplitude (top) at two seismograph stations in South Iceland, SAU and ASM, and the magnitude of earthquakes at Hekla (bottom). From Soosalu et al (2003). Reproduced with the permission of the copyright holder, Springer Nature.…”
Section: Grímsvötnmentioning
confidence: 99%